Integrasi-Interkoneksi Amin Abdullah dan Relevansinya dalam Kajian Ilmu-Ilmu Sosial - Yusuf, Muhammad Zulfikar (Universitas Muhammadiyah Yogyakarta, 2025)
One of the main problems in the current scientific context is the tendency for a dichotomy between religion and science, especially in the study of social sciences, which causes scientific exclusivity and gaps in understanding and solving human problems. Islam emphasizes the importance of integration between religion and science as an answer to the complex problems of human life today. Therefore, this research examines Amin Abdullah's thoughts on the integration-interconnection paradigm and its relevance to various social science disciplines. This research uses a qualitative descriptive approach with a library research method to analyze the idea of integration-interconnection developed by Amin Abdullah. The integration-interconnection paradigm combines various perspectives from two or more scientific disciplines to increase in-depth understanding and offer solutions to complex problems. Amin Abdullah emphasized the importance of cross-disciplinary collaboration to avoid dichotomy and exclusivity. This research shows that the integration-interconnection paradigm is very relevant in solving human problems, especially in the study of social sciences such as economics, law, and politics, while remaining based on universal and inclusive Islamic principles.